Management Analysis of Sleman Regency Local Government Operational Asset Management - Rifki Khoirudin (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The background of this research is the management of operational vehicle assets for the Government of Sleman Regency and according to previous research there is a phenomenon of official vehicles that are still lacking in management, especially in maintenance, their use has not been carried out regularly. The Sleman Regency Government also has phenomena regarding operational service vehicle assets that are stalled or are no longer used. This study aims to determine whether the operational service vehicle asset management is in accordance with the Minister of Home Affairs Regulation number 19 of 2016 concerning the management of regional property. The research method uses descriptive research methods and qualitative approaches. Using primary data and data collection techniques are literature/documentation studies, interviews and drawing conclusions. The results of the research show that it is not in accordance with the management of official vehicle assets in accordance with the Minister of Home Affairs Regulation number 19 of 2016 concerning the management of regional property. It can be seen from the limited human resources so that management is lacking. Suggestions that can be given are to increase human resources and complete administration in the management of operational official vehicles.